STANDARDS AND REQUIREMENTS OF PROFESSIONAL EDUCATION AND DEVELOPMENT OF FOREIGN LANGUAGE TEACHERS IN THE USA - Levrints, M.I (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2019)
The paper examines issues of professional standards underpinning foreign language teacher education and development in the USA; also, the content of standards and approaches to their formulation are elucidated; next, current efforts at implementing standards-oriented teacher education are discussed. The vision and stance of the American educational community in standards related debates are explored. It is argued that standards setting endeavors concerning preparation, licensing and certification of teachers in the USA catalyze systematic transformations of teacher education mainstream practices, promoting teaching and learning outcomes through indirect influence on professional competence of pedagogues. Structurally, the system of professional standards is three-componential: standards related to accreditation of teacher preparation programs, reflecting competence requirements for newly graduated teachers; licensing standards targeted at novice teachers (with teaching experience less than three years); certification standards as recognition of outstanding performance and proficiency in teaching. The recent trend evolving in the result of standards elaboration efforts in the country has become the involvement of practicing foreign language teachers in all decisions pertaining to the definition of mission, content and realization of standards-based education. Extent research gives hints that standards oriented teacher education promotes its educational potential, as shown by empirical evidence.